A review on the latest advances in extraction and analysis of artemisinin - Nahar, Lutfun; Guo, Mingquan; Sarker, Satyajit D (Phytochemical analysis, 2020)
INTRODUCTION: Artemisinin (1), a well-known natural antimalarial drug, is a sesquiterpene lactone that contains a unique peroxide bridge. Since its discovery, the amount of research into the analysis of artemisinin has increased considerably, and it has been further intensified since the Noble Prize win by Tu Youyou in the year 2015 for the discovery of artemisinin. OBJECTIVE: To review literature on the extraction and analysis of artemisinin, published during 2017-present, and to present an appraisal of those methods. METHODOLOGY: Extensive literature search was carried out which involved, but not limited to, the use of, various databases, like Web of Knowledge, PubMed and Google Scholar, and relevant published materials including published books. The keywords used, in various combinations, with artemisinin being present in all combinations, in the search were artemisinin, Artemisia annua, analysis, extraction, quantitative, qualitative and quality control. RESULTS: During the period covered in this review, several methods of analysis of artemisinin have been reported, the most of which were liquid chromatography (LC)-based methods. However, the use of new methods like near-infrared analysis, fluorometirc analysis and molecular imprinting, and a significant increase in the use of computational tools have been observed. Mainly several methods involving supercritical fluid extraction and ultrasound-assisted extraction of artemisinin have dominated the extraction area. CONCLUSIONS: Newer analytical tools, as well as improved protocols for the known analytical tools, for qualitative and quantitative determination of artemisinin (1), have been made available by various researchers during the period covered by this review. Supercritical fluid extraction and ultrasound-assisted extraction are still the methods of choice for extraction of artemisinin.
Keywords: Plant Extracts; rostlinné extrakty; Tu Youyou; supercritical fluid extraction; Artemisinins; Antimalarials; LC-MS; antimalarika; analysis; artemisinin; artemisininy; Artemisia annua; HPLC; Chromatography, Liquid; ultrasound-assisted extraction; Nobel prize; chromatografie kapalinová; extraction